ANALISIS FRAMING MEDIA CNN INDONESIA TERHADAP KETERLIBATAN PRESIDEN JOKOWI DALAM PILGUB SUMATERA UTARA 2024 - Roiisul Ibaad Aunillah; Dyva Claretta (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
The 2024 North Sumatra gubernatorial election has become a political event that draws significant public attention, particularly due to the involvement of President Joko Widodo’s (Jokowi) family, namely Bobby Nasution. In a democratic system, the mass media plays a crucial role as one of the pillars of democracy serving as a watchdog of power, a conveyor of information, and a shaper of public opinion. This study employs a qualitative approach using the framing analysis model developed by Pan and Kosicki, in conjunction with the social construction theory proposed by Peter Berger and Thomas Luckmann. The analysis is based on Pan and Kosicki’s model, which includes four structural elements: syntactic, script, thematic, and rhetorical structures. The research utilizes news articles published by CNN Indonesia between July and November 2024 as the data sample. The findings reveal that CNN Indonesia does not present a fully neutral portrayal of the political reality. The news outlet constructs Bobby Nasution's image as a young figure with strong connections to central power. CNN Indonesia frames the issue in a complex manner, adhering to journalistic principles while still incorporating political narratives that have the potential to shape public opinion on the alleged nepotistic practices of President Jokowi in the 2024 North Sumatra gubernatorial election.